2018
DOI: 10.1590/s0004-2803.201800000-72
|View full text |Cite
|
Sign up to set email alerts
|

Target, Prescription and Infusion of Enteral Nutritional Therapy of Critical Patients in Intensive Care Unit

Abstract: BACKGROUND: Enteral nutritional therapy (ENT) is the best route for the nutrition of critically ill patients with improved impact on the clinical treatment of such patients. OBJECTIVE: To investigate the energy and protein supply of ENT in critically ill in-patients of an Intensive Care Unit (ICU). METHODS: Prospective longitudinal study conducted with 82 critically ill in-patients of an ICU, receiving ENT. Anthropometric variables, laboratory tests (albumin, CRP, CRP/albumin ratio), NUTRIC-score and Nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 29 publications
0
5
0
10
Order By: Relevance
“…(CHELKEBA, et al, 2017;COVELLO, et al, 2020;DAVARI et al, 2019;GOSTYŃSKA, et al, 2019;MCCLAVE, et al, 2016;PADILLA, et al, 2019;PAZ;COUTO, 2016;SINGER, et al, 2018) A implementação deste suporte ocorreu em 69,6% dos pacientes, tal resultado foi inferior à achados na literatura. (AZEVEDO, et al, 2019;JOSÉ, et al 2018;NUNES, et al, 2018;WEI, et al, 2015) No atual trabalho, a oferta de dieta em período precoce nos pacientes internados foi associada a uma maior adequação calórico-proteica durante a primeira semana de internamento e a um menor tempo de permanência na UTI. O suporte nutricional precoce é uma terapia que tem sido bem estabelecida diante do cenário do paciente crítico, tornando-se uma ferramenta que ajuda a atenuar as alterações metabólicas, diminuir a incidência de complicações infecciosas, bem como reduzir o tempo de internação e a mortalidade dos pacientes.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…(CHELKEBA, et al, 2017;COVELLO, et al, 2020;DAVARI et al, 2019;GOSTYŃSKA, et al, 2019;MCCLAVE, et al, 2016;PADILLA, et al, 2019;PAZ;COUTO, 2016;SINGER, et al, 2018) A implementação deste suporte ocorreu em 69,6% dos pacientes, tal resultado foi inferior à achados na literatura. (AZEVEDO, et al, 2019;JOSÉ, et al 2018;NUNES, et al, 2018;WEI, et al, 2015) No atual trabalho, a oferta de dieta em período precoce nos pacientes internados foi associada a uma maior adequação calórico-proteica durante a primeira semana de internamento e a um menor tempo de permanência na UTI. O suporte nutricional precoce é uma terapia que tem sido bem estabelecida diante do cenário do paciente crítico, tornando-se uma ferramenta que ajuda a atenuar as alterações metabólicas, diminuir a incidência de complicações infecciosas, bem como reduzir o tempo de internação e a mortalidade dos pacientes.…”
Section: Discussionunclassified
“…Em outro estudo, ficou evidente a dificuldade em alcançar as metas nutricionais, pois 89,09% não atingiram o mínimo de 80% para meta energética e 98% não atingiram o mínimo de 80% para meta proteica. (JOSÉ, et al, 2018) Na literatura existem divergências em relação a valores tidos como adequados em relação à ingestão calórica e proteica a ser fornecida aos pacientes críticos. (AL-DORZI et al, 2016;DAVARI et al, 2019;TOLEDO;CASTRO, 2019) Entretanto, a ingestão calórico-proteica insuficiente pode agravar a condição clínica do paciente.…”
Section: Discussionunclassified
“…Na TN, a TNE é a primeira via de escolha para a alimentação artificial do paciente crítico pela sua proximidade com a via fisiológica, praticidade no manejo pela equipe assistencial, pelos baixos riscos associados ao seu uso, bem como pela oportunidade de manutenção do trofismo intestinal, e consequentemente, de um microbioma que auxilie na condição de equilíbrio orgânico sistêmico (ESPEN, 2019;JOSÉ, LEANDRO-MEHRI, AQUINO, 2018;BRASPEN, 2018;TOLEDO 2017;FONSECA, COSTA, 2010).…”
Section: Terapia Nutricional Enteral No Paciente Graveunclassified
“…In the case of critically ill in-patients, considering that this is the evidence base that we have available for decision-making with regard to Covid-19 critical patients, in general, the clinical evolution with high mortality rates can occur, especially if we consider malnourished patients and those with increased infections, complications, hypermetabolism and longer hospital stay, who can often have low energy and protein intake when fed by nutritional therapy [36][37][38][39][40][41][42][43]. When they are undergoing nutritional therapy, it is observed that these critical patients are unable to reach the goals that were defined for energy and proteins, and there is an influence of the energy and protein deficit on the length of hospital stay and mortality [40,44,45]. A study showed that critically ill patients on mechanical ventilation, with energy and protein adequacy were associated with a tendency to an increased mortality in 60 days [46].…”
Section: N U T R I T I O N a L T H E R A P Y I N C R I T I C A L P A mentioning
confidence: 99%